Design of a Galvanic Vestibular Stimulation based Collision Avoidance System for the Visually Impaired - Quevedo, Paul (My University, 2010)
To date many different attempts at assisting the visually impaired navigate busy environments have been explored. Most systems use an array of sensors to map the environment around the subject and by use of auditory cues or wearable vibrators, indicate which direction the subject should move in to avoid a collision. This report outlines the design of a system to use Galvanic Vestibular Stimulation as another modality to manoeuvre subjects from a collision course.
Bipolar Galvanic Vestibular Stimulation (GVS) entails the use of a low frequency, low amplitude current, typically 1mA, passed between the mastoid processes of a person causing a sensation of imbalance towards the anodal electrode. It is an already established method of altering a person‟s balance and has been found to affect the trajectory of a person walking in a given direction.
The design of the system is a network of microcontrollers in which a control unit collects data from sensors, builds a map of the environment, determines the optimal direction to proceed and controls the current stimulator to deliver the desired GVS. Using the Controller Area Network (CAN) protocol allows for a highly modular system design in which any type of sensor or data node can easily be added or removed from the system.
The system was prototyped and tested. Initial results indicate the system is capable of navigating a person from a trajectory course however several issues are encountered in quantifying the systems effectiveness. All subsystems performed as desired however certain ones were found to be over engineered for the task required. The results of the systems performance are discussed and areas for improvement highlighted.
Keywords: Biomedical; Electrical and Computer Engineering; Biomedical